Exploring Mathematical Concepts in Rebana Art: An Ethnomathematical Approach for Junior High School Learning - Ramadhani, Putri; Subchi, Muhammad; Silviani, Ana Mega (Interval: Indonesian Journal of Mathematical Education, 2025)
Purpose of the study: This study aims to identify ethnomathematical concepts in rebana art related to one-dimensional, two-dimensional, and three-dimensional geometry, arithmetic sequences, and integer operations. Furthermore, this study also seeks to test the potential of rebana art as a source of mathematics learning for junior high school students. Methodology: The data obtained were qualitative, while the sources were obtained from observations, interviews, and documentation related to the Rebana Art. The instrument in this study was the researcher herself. The tools used were interview guidelines, observations, and documentation. Data validity techniques were carried out through triangulation through checking method triangulation, source triangulation, and time triangulation, with the data analyzed descriptively qualitatively. Main Findings: The findings show that rebana art contains ethnomathematic concepts related to one-dimensional, two-dimensional, and three-dimensional geometry through measurement activities, including angles, circles, rectangles, cylinders, and cones. The concept of arithmetic sequences is identified in Qasidah rebana, while integer operations appear in Hadrah rebana performances. Furthermore, rebana art can be aligned with the curriculum as a source of mathematics learning for Grades VII, VIII, and IX. Novelty/Originality of this study: This study offers a new contribution by systematically mapping specific mathematical topics across different types of tambourine arts and explicitly aligning them with lower secondary school curriculum levels. This study advances ethnomathematics research by showing how local musical traditions can be transformed into structured mathematical learning resources grounded in formal curriculum standards.